The Problems of Translation Nature and Place of Abdullah Qadiri's Novel "Days Gone By” in English - Hikmatova Muqaddas Nurillayevna; Kobilova Feruza (International Journal on Integrated Education, 2022)
The depiction of natural landscapes given in works of art is one of the factors that demonstrate the creative artistic skill. Because in the depiction of natural landscapes, the artist's attitude to the space he captures, how much he knows the place, how deeply he feels the world of heroes and the environment in which they live. Therefore, the depiction of natural landscapes is an integral part of the work of art.